Influence of different test conditions on the emotional responses elicited by beers. (July 2020) - Worch, Thierry; Sinesio, Fiorella; Moneta, Elisabetta; Abbà, Silvia; Dreyfuss, Lise; McEwan, Jean A.; Porcherot-Lassallette, Christelle
Highlights: Different beers are tested in different test situations simulating a real pub experience. The emotional responses were measured in each situation using CATA. The relative importance of the samples, test situation and test settings were measured. The samples and test situations may generate different emotion responses. The test setting (presentation order) has a fairly consistent impact on emotion responses. Abstract: In the last decade, considerable interest was given to the measurement of emotional responses to samples. Such measures were designed to go beyond liking and better understand how the actual product, with or without a context, could elicit positive of negative emotions that help inform overall product performance. Products can be optimised according to their emotions profile as well as their sensory profile, and such information is valuable from a marketing point of view as it opens new doors for advertising, claims, etc. What needs further investigation is how relevant and how valid this information is. In recent studies, it was argued that emotional responses are not so much driven by the samples themselves, but by the context gravitating around the samples and around the assessors. To better understand the consumers' self-reported emotional responses, the same 4 beer samples were evaluated in 5 different test conditions including a Central Location Test, a real and a re-created pub, and 2 Virtual Reality situations (VR goggles projecting a 360° video and VR combining 3D modelling and 360° photos) simulating a pub experience. For each condition, a CATA task including 11 emotion terms was performed by just over 100 consumers. The direct impact of the samples on the emotional responses were first evaluated overall, before being compared between test conditions and using the test settings (presentation order). The results show that although the samples were quite similar, they conveyed different emotional responses to the consumers. However, these emotional responses seem less strong than the one conveyed by the different test situations, or even the test settings. The presentation order, for instance, appears to play an important and consistent role on the emotional responses.